Inhibition of retrograde transport modulates misfolded protein accumulation and clearance in motoneuron diseases. Issue 8 (3rd August 2017) - Cristofani, Riccardo; Crippa, Valeria; Rusmini, Paola; Cicardi, Maria Elena; Meroni, Marco; Licata, Nausicaa V.; Sala, Gessica; Giorgetti, Elisa; Grunseich, Christopher; Galbiati, Mariarita; Piccolella, Margherita; Messi, Elio; et al.
ABSTRACT: Motoneuron diseases, like spinal bulbar muscular atrophy (SBMA) and amyotrophic lateral sclerosis (ALS), are associated with proteins that because of gene mutation or peculiar structures, acquire aberrant (misfolded) conformations toxic to cells. To prevent misfolded protein toxicity, cells activate a protein quality control (PQC) system composed of chaperones and degradative pathways (proteasome and autophagy). Inefficient activation of the PQC system results in misfolded protein accumulation that ultimately leads to neuronal cell death, while efficient macroautophagy/autophagy-mediated degradation of aggregating proteins is beneficial. The latter relies on an active retrograde transport, mediated by dynein and specific chaperones, such as the HSPB8-BAG3-HSPA8 complex. Here, using cellular models expressing aggregate-prone proteins involved in SBMA and ALS, we demonstrate that inhibition of dynein-mediated retrograde transport, which impairs the targeting to autophagy of misfolded species, does not increase their aggregation. Rather, dynein inhibition correlates with a reduced accumulation and an increased clearance of mutant ARpolyQ, SOD1, truncated TARDBP/TDP-43 and expanded polyGP C9ORF72 products. The enhanced misfolded protein clearance is mediated by the proteasome, rather than by autophagy and correlates with the upregulation of the HSPA8 cochaperone BAG1. In line, overexpression of BAG1 increases the proteasome-mediated clearance of these misfolded proteins. Our data suggest that when the misfolded proteins cannot be efficiently transported toward the perinuclear region of the cells, where they are either degraded by autophagy or stored into the aggresome, the cells activate a compensatory mechanism that relies on the induction of BAG1 to target the HSPA8-bound cargo to the proteasome in a dynein-independent manner.